2020
DOI: 10.37934/arfmts.69.2.130146
|View full text |Cite
|
Sign up to set email alerts
|

Natural Ventilation in Passive System of Vertical Two-Stores Solar Chimney

Abstract: The present work includes a numerical study that investigated in a thermal performance of the passive system of a vertical two stores solar chimney. A several models of a vertical solar chimneys were designed, by using the solid work 18 software, that then brought to the Ansys Fluent 18.2 software for simulation, under (Al-Kut, Iraq) city climatic conditions on the hot summer day of (5-8-2018). This simulation was comprised of a five testing models of a two stores solar chimney that oriented to the south and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…al. (2020) [5] statistically explored the natural ventilation in twostory buildings using a vertical two-story SC passive system by using ANSYS fluent. The results showed that the long vertical SC might provide the optimum NV while also causing a visible rise in inside temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…al. (2020) [5] statistically explored the natural ventilation in twostory buildings using a vertical two-story SC passive system by using ANSYS fluent. The results showed that the long vertical SC might provide the optimum NV while also causing a visible rise in inside temperatures.…”
Section: Introductionmentioning
confidence: 99%